Au cœur du bouleau (Betula spp.) et de la conservation en Abitibi-Témiscamingue (Québec, Canada) - Michel Rapinski; Alain Cuerrier (Revue d'ethnoécologie)
The forestry industry is crucial to the economy of Canada and Quebec in particular, which contributes significantly to this sector. Birches (Betula spp.) are the most important deciduous species in the Quebec region of Abitibi-Témiscamingue, where the Anishinabe peoples play a role in managing this resource. However, management and land use conflicts arise around a fundamental question: « Which forest specie(s) are we managing? » If the answers provided by the forestry industry and Indigenous peoples are not necessarily in harmony with each other, the importance given to them necessitates a reflection grounded in an anthropology of the environment and conservation that ultimately answers the questions: « Why name? » and « Why classify? » Indeed, the botanical classifications of birches in North America are complex and controversial, and the forestry industry often does not consider the distinction between certain species, such as the paper birch (Betula papyrifera Marshall) and the heartleaf birch (Betula cordifolia Regel), as economically relevant. However, a review of birch nomenclature by Peoples of the Algonquian linguistic family reveals a fine distinction between birches based on morphological, environmental, and/or functional criteria. These criteria fit into classification logics that do not strictly mirror the classifications of botanists or foresters. Nevertheless, they are essential for preserving and transmitting the ancestral knowledge and practices of the Algonquian peoples. Thus, their consideration is important for mutualizing the management and the conservation of the environment, with the preservation of the cultural heritage of the peoples who depend on it.